Application of Reflectance Transformation Imaging (RTI) to surface bone changes in paleopathology - Morrone, Alessandra; Pagi, Hembo; Tõrv, Mari; Oras, Ester (Anthropologischer Anzeiger, 2021)
The analysis of surface bone changes is an essential aspect of the paleopathological examination of skeletal remains from archaeological and forensic contexts, and proper digital imaging is an indispensable aspect of the documentation of bone modifications. This paper evaluates the applicability of Reflectance Transformation Imaging (RTI) to the study of pathological bone surface changes in human remains. Forty-five samples of human bones and teeth from medieval and early modern Estonian cemeteries were photographed and subjected to RTI imaging to document the pathological conditions that typically result in subtle surface modifications. Subperiosteal Bone Production (SBP), abnormal porosity, cribra orbitalia, endocranial lesions and lytic lesions in bone, as well as enamel hypoplasia and dental calculus in teeth were successfully represented with this technique. The results indicate that RTI allows visualization of shallow and discrete bone changes that are otherwise unnoticed. In some cases, this technique provides a better understanding of the nature and development of particular pathological processes than possible with conventional imaging. Although it cannot entirely replace microscopic and radiological techniques, RTI can be successfully performed in a reasonably short time by non-specialist operators with limited funding and resources, thus enabling identification of specimens that should be subject to more expensive or time-consuming analyses. Hence, RTI constitutes a valuable tool for the representation of subtle surface details in pathological bone, and can successfully support standard photography in paleopathological studies, museum display and scientific communication.